Education to Increase Knowledge and Attitudes of Teenagers About HIV-AIDS Using Digital Storytelling Media and Leaflets at the Kalasey Agricultural Development Vocational School - Samsudin, Irmawati; Desyani, Ni Luh Jayanthi; Laoh, Joice Mermy; Alam, Syamsu Alam,; Raule, Jean Henry (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2024)
Introduction : Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells and weakens the human immune system. Meanwhile, Acquired Immune Deficiency Syndrome (AIDS) is a group of symptoms that arise due to weakening of the immune system caused by infection with HIV. Adolescence is the peak transition period which is at risk of sexual behavior and delinquency because the emotional state of teenagers is still unstable, wanting to try something new and their curiosity is high. Having knowledge about HIV-AIDS can influence teenagers to act according to the knowledge they have gained. Good knowledge will have an impact on good attitudes as well. Digital storytelling is a modern learning media that combines various types of learning media, namely images, music, stories and sound. and what is unique is that digital storytelling can be provided in digital form and then uploaded to various social media platforms, so that digital storytelling can be accessed by anyone, anytime, anywhere, and in various conditions. Research objective : to determine the effect of education on increasing teenagers' knowledge and attitudes about HIV-AIDS using digital storytelling and leaflet media at the Kalasey State Agricultural Development Vocational School. Method : This research design used a Quasy Experiment with 84 teenagers from the Kalasey State Agricultural Development Vocational School as samples, selected through simple random sampling. Conclusion : The results of the Wilcoxon test show that the knowledge value is Pvalue = 0.008 or (P <0.05) and the attitude value is Pvalue = 0.000 or (P <0.05). So it can be said that there is an educational influence on increasing teenagers' knowledge and attitudes about HIV-AIDS using digital storytelling media at Kalsey State Agricultural Development Vocational School. Keywords : Knowledge; Attitude; Teenagers; Digital Storytelling